Pengaruh Green Banking, Sustainability Reporting, dan Kualitas Laba Terhadap Kinerja Perusahaan pada Bank Umum Konvensional di Indonesia (Periode 2020–2024) - Lusiva Pardosi; Fathihani (Jurnal Ilmiah Literasi Indonesia, 2025)
This study aims to analyze the effect of Green Banking, Sustainability Reporting, and earnings quality on corporate performance in conventional banks in Indonesia during the 2020–2024 period. This research employs a quantitative approach with a causal design. The independent variables include Green Banking, Sustainability Reporting, and earnings quality, while the dependent variable is corporate performance measured by Return on Equity (ROE). The research population consists of 68 banks listed on the Indonesia Stock Exchange, and through purposive sampling, 22 banks were selected over five observation years, resulting in 110 total samples. The data used are secondary data analyzed with descriptive statistics, classical assumption tests, and multiple regression using SPSS 26. The findings reveal that: (a) Green Banking has a significant effect on corporate performance, indicating that the implementation of environmentally friendly banking practices in bank operations can enhance profitability; (b) Sustainability Reporting significantly affects corporate performance, suggesting that sustainability disclosure improves investor trust, corporate reputation, and transparency in managing environmental, social, and governance aspects; (c) earnings quality significantly influences corporate performance, indicating that profits derived from real operational activities and free from accounting distortions strengthen bank profitability.